Geophagy: a survey on the practice of soil consumption in N'Djamena, Chad - Djimadoum Kimassoum; Ngum Lesley Ngum; Mahamat Bechir; Alexis Haroun; Abdelsalam Tidjani; Chiara Frazzoli (Inishmore Laser Scientific Publishing Ltd, 2023)
# Background Geophagy, the recurrent intentional eating of soil, is well documented in many African countries, but little or nothing is known about this practice in Chad. We conducted a cross-sectional study among inhabitants of N'Djamena to assess: (i) source, type, and form of geophagic soil at purchase; (ii) event, daily frequency, daily cost, and duration of soil eating; (iii) habits at consumption and storage; (iv) specific motivation of soil eating and habit-forming events; (v) expected health benefits and awareness of health risks; and (vi) chance for intervention. # Methods One main food market was randomly selected in each of the 10 districts of N'Djamena. In each food market, 10 vending points of geophagic soil were randomly selected. In each vending point, one geophagist was interviewed. A total of 100 geophagists (residents in N'Djamena) completed a self-reported structured questionnaire on hard copy. Outcomes were analyzed using IBM SPSS statistics 20.0 software. # Results The main group of geophagists in Chad is represented by women in childbearing age (30.4 years old). Geophagic soil is generally locally extracted and easily available at the food market (77%). Kaoline is the most consumed soil (63%) followed by laterite (29%). Soil is preferentially consumed granulated (66%) or crushed (23%), but also in powder. Protective effect against cancer and gastritis figures out as main (35%) expected benefit of the practice, followed by protection against nausea and vomiting (25%) and pain (19%). One in 4 geophagists eats soil due to pleasure at taste, and some (2%) just follow the habit without specific purpose of pleasure. Geophagy in Chad is a culturally-transmitted form of pica. Interestingly, even if the vast majority of geophagists (94%) is unaware and uninformed about health risks of soil eating, the 43% were against the option of recommending it. # Conclusions Based on these findings, we recommend awareness campaigns on: (i) the health risk of soil eating, (ii) erroneous beliefs, e.g., the protective effect of geophagic soil against cancer, and (iii) the misleading communication subtended by the vending of soil among food items.